Vestibular Cochlear Manifestations in COVID-19 Cases - Kaliyappan, Kathiravan; Chen, Yu-Chen; Krishnan Muthaiah, Vijaya Prakash (Frontiers in Neurology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a high transmissible infectious disease that primarily impacts the respiratory system and leads to death as it worsens. Ever since the World Health Organization declared the disease as a global pandemic, the pathophysiology, clinical manifestations, and disease prognosis has been discussed in various literature. In addition to impaired respiratory health, the symptoms also indicated the involvement of the cardiovascular and neurological system after SARS-CoV-2 infection. Despite the pulmonary, cardiovascular, and neurological complications, many reports also revealed the prevalence of vestibulocochlear symptoms like dizziness, vertigo, vestibular neuritis, sudden sensorineural hearing loss, and tinnitus. Though many clinical reports and scientific reviews reported the vestibular and cochlear impairments associated with coronavirus disease 2019 (COVID-19) infection, the underlying pathological mechanisms are still unclear and unexplored. In this review, we discussed the published clinical reports, research articles, and literature reviews related to vestibulocochlear manifestations following SARS-CoV-2 infections. We also summarized the current knowledge about the prevalence, epidemiological and clinical features, and potential pathological mechanisms related to vestibular and cochlear manifestations resulting from COVID-19 infections.